ANALISIS PENETAPAN NILAI JUAL OBJEK PAJAK TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN MINAHASA TENGGARA - Watak, Nola Lavenia (ACCOUNTABILITY, 2015)
Property Tax is one tax which is managed by the local government. Which is the only property tax in Indonesia, because most of the revenue is income areas, among others, are also used for the provision of facilities enjoyed by the central government and local government. Bases of land and building tax is the taxable value. The purpose of this study is to analyze Determination of taxable value against land and building tax in Southeast Minahasa Regency. The object of this research is 3 Southeast Minahasa District in the District Ratahan, District Pasan, and the District of East Ratahan. The data collection techniques in this study is a field study in the Department of Revenue in Southeast Minahasa regency. This research uses descriptive method. Based on the research results, the authors concluded that the three districts are districts Ratahan, Pasan, and Ratahan East where the districts are located in the city center in Southeast Minahasa Regency, strategic location and generates economic value. So it has a high contribution to the reception in Southeast Minahasa regency. Department of Revenue is responsible for determining the tax object selling value needs to improve the assessment and pengelolahan data, especially between the sale value of the tax object selling prices that occurred in the community so that more relevant determination.